The effects of adding lactic acid bacteria and cellulase in oil palm (Elaeis guineensis Jacq.) frond silages on fermentation quality, chemical composition and in vitro digestibility - Ebrahimi, Mahdi; Rajion, Mohamed Ali; Goh, Yong Meng; Farjam, Abdoreza Soleimani; Sazili, Awis Qurni; Schonewille, Jan Thomas (PAGEPress, 2014)
The main objective of the current study was to evaluate whether oil palm frond (OPF) can be successfully ensiled without or with the additives cellulase or lactic acid bacteria (LAB). Thus, fresh OPF was ensiled either without additives or with cellulase or LAB or their combination. Ensiling was carried out by storing 2 kg samples in airtight glass jars at 25-30°C for 12 weeks. Thereafter, the silage samples were subjected to proximate analyses, an in vitro digestibility assay and measures on selected indices of fermentation. Fermentation of OPF without additives appeared to be unsuccessful as both pH and ammonia content were too high (4.9 and 9.9%, respectively). In contrast, the use of cellulase or LAB resulted in silages with a pH<4.5 and ammonia fractions <8.4%, but the lowest values were found when both cellulase and LAB were used, i.e. pH=4.1 and ammonia fraction=6.7%. In vitro digestibility of dry matter was significantly higher in the cellulase treated silages. The process of ensiling was associated with both a significant decrease of the fat content of OPF and a significant change of the fatty acid profile. However, the proportions of major fatty acids (C16:0 and C18:2n-6) were not affected by the process of ensiling. In conclusion, the use of cellulase additive appears a practical tool to safeguard the process of fermentation. Using a cellulase enzyme or its combination with LAB improves the fermentation profile and increases the nutritional value of the OPF silage.